DIGITAL LEARNING AND TRANSFORMATION OF EDUCATION (TECHNICAL SCIENCE RESEARCH IN UZBEKISTAN, 2024)
This article explores the problems faced during the digital transformation of the educational system and solutions to these challenges are also discussed. It argues that digital technology, including AI, could improve the effectiveness and quality of education by personalising education, be it teaching and learning or other education services, by making it more inclusive and possibly equitable, and by improving the cost-efficiency of the sector. By addressing these issues, the educational system can fully leverage the benefits of digital transformation to enhance teaching and learning outcomes.